Decellularized In Vitro Capillaries for Studies of Metastatic Tendency and Selection of Treatment - Outi Huttala; Desiree Loreth; Synnöve Staff; Minna Tanner; Harriet Wikman; Timo Ylikomi (Biomedicines, 2022)
Vascularization plays an important role in the microenvironment of the tumor. Therefore, it should be a key element to be considered in the development of in vitro cancer assays. In this study, we decellularized in vitro capillaries to remove genetic material and optimized the medium used to increase the robustness and versatility of applications. The growth pattern and drug responses of cancer cell lines and patient-derived primary cells were studied on decellularized capillaries. Interestingly, two distinct growth patterns were seen when cancer cells were grown on decellularized capillaries: “network” and “cluster”. Network formation correlated with the metastatic properties of the cells and cluster formation was observed in non-metastatic cells. Drug responses of patient-derived cells correlated better with clinical findings when cells were cultured on decellularized capillaries compared with those cultured on plastic. Decellularized capillaries provide a novel method for cancer cell culture applications. It bridges the gap between complex 3D culture methods and traditional 2D culture methods by providing the ease and robustness of 2D culture as well as an in vivo-like microenvironment and scaffolding for 3D cultures.